FINANCIAL PERFORMANCE ANALYSIS ON KSP TRI DHARMA ARTHA SEPUTIH RAMAN. - Suwarto Suwarto (FIDUSIA : JURNAL KEUANGAN DAN PERBANKAN, 2018)
This research is motivation to know the financial performance of ksp so that the management of the ksp can perform their duties and obligations well in accordance with the objectives of the cooperative in general.The purpose of this study to determine the financial performance of ksp based on the ratio of Liquidity, Solvency and Profitability on Tri Dharma Cooperative Artha Seputih Raman.Based on the it can be concluded the financial performance of Savings and Loans Cooperative Tri Dharma Artha Seputih Raman years in 2012-2016 are:The liquidity ratio consisting of current ratio yielded an average of 90.44%. It can be concluded that current ratio includes bad criteria because less than 125%. Solvency ratio consists of debt to asset ratio yield average of 91,42% and can be concluded debt to asset ratio including criterion less good, because bigger than 60% to 95%. While based on the calculation of debt to equity ratio produce an average of 1,074.05%, it can be concluded debt to equity ratio including bad criteria because greater than 200% and profitability ratio consisting of return on assets (ROA) yield average of 1 , 36%, can be concluded return on assets (ROA) including criteria less good because more than 1% to 3% whereas based on calculation of return on equity (ROE) yield average of 16,04%, can be concluded return on equity ( ROE) is included in good criteria because it is greater than 15% to 21% and based on the calculation of net profit margin (NPM) yields an average of 8.08%, net profit margin (NPM) is considered good enough criteria as more than 5% to 10%.Keywords: Financial Statement, Liquidity Ratio, Solvency Ratio, and Profitability Ratio